LATE PLEISTOCENE-HOLOCENE PALEOLIMNOLOGY OF THREE NORTHWESTERN RUSSIAN LAKES - Davydova N.N.; Subetto D.A.; Khomutova V.I.; Sapelko T.V. (My University, 2001)
The vegetation history and development of three different types of lakes, lakes Valday, Kubenskoye and Vishnevskoye (northwest of the East European Plain) were reconstructed using paleolimnological techniques. Watershed vegetation demonstrates a close connection with climate fluctuations: gradual expansion of the southern broad-leaved trees to the North during the Holocene with the maximum extent during the climate optimum (8000–5000 BP); and their subsequent retreat afterwards; followed by the extension of spruce during the cold and dry Subboreal time; and dominance of pine-spruce-birch forests in the Subatlantic time. The Late Pleistocene and Holocene climate changes resulted in lake-level fluctuations and other ecosystem changes. Valday Lake was formed ca. 12,500 BP as an oligotrophic, deep water basin. The lake level decreased during the dry Boreal, then increased again during the humid Atlantic period. The large shallow Kubenskoye Lake was formerly a part of an ice margin lake, which was then separated (ca. 13,000 BP) and developed into the Sukhona Basin with an outflow to the northwest. During the Atlantic, the outflow direction changed to the east. As a result, the ancient Sukhona Lake disappeared and Kubenskoye Lake formed in its modern size and shape. Vishnevskoye Lake, on the Karelian Isthmus, was formed at the beginning of the Preboreal after the disappearance of the Baltic Ice Lake. It was flooded by waters of the Boreal Ancylus transgression of the Baltic Basin and had become a small eutrophic lake by the time.
Keywords: Holocene; Pleistocene; paleolimnology; sediments; diatoms; pollen; paleoclimatic changes; Russia; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Holocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен